Skill training for social workers : a manual - Datar, Sudha (SAGE, 2010)
Skill Training for Social Workers: A Manual, responds to the demand for indigenous textbooks and teaching materials for social work educators, scholars and students. Unlike theory books of social work which list the skills required for the practice of social work methods but do not enable the development of these skills, this manual bridges the gap by providing concrete exercises for the development of method-linked skills. Some of its main features are: - Includes theoretical inputs, games and exercises on the theme of understanding perception, self-awareness, sensitivity, communication and working with individuals and groups. - Covers a variety of topics, role plays, songs, case studies, street plays and exercises on self-awareness, self-development, SWOT analyses, communication, goal setting, time management and stress management. - Allows for flexibility to adapt modules to the local realities, drawing from students' field experiences and using indigenous agency case records or material.